Cost-effectiveness of internet-based cognitive-behavioural therapy for obsessive-compulsive disorder - Osborne, Debra (Internet Interv, 2019)
Economic analyses of treatments for OCD have been limited. This study analysed the comparative economic benefits and costs of an internet-based CBT (iCBT) relative to internet-based progressive relaxation therapy (iPRT) control. These were benchmarked against current estimates for face-to-face CBT (ffCBT) sourced from literature. The benefits to society of providing increased access to treatment was assessed using a cost-benefit analysis based upon productivity gains arising from treatment. Identification of the most cost-effective treatment amongst the three treatments was assessed using a cost-effectiveness analysis based upon both effectiveness as measured by the Yale-Brown Obsessive Compulsive Scale (YBOCS) and percentage of responders. The cost-effectiveness analysis showed iCBT to be the most cost effective treatment of the three analysed, followed by ffCBT based upon percentage of responders and iPRT based upon overall effectiveness of treatment. The cost-benefit analyses showed all treatment options delivered substantial benefits to society. These benefits ranged from three to thirty-five times the cost of providing treatment, depending on the assumptions used and the treatment provided, with iCBT showing the greatest ratio of benefits to costs but the ffCBT providing the greatest absolute benefits. Overall, the findings provide support for increased access to CBT intervention, for all patients with OCD; with online therapist-assisted modes of delivery as a cost-effective alternative to existing face-to-face treatments. Further work to more accurately quantify the benefits and costs resulting from CBT treatment modalities is required to support these preliminary findings.